Revolutionizing migraine management: advances and challenges in CGRP-targeted therapies and their clinical implications - Özge, A.; Baykan, B.; Bıçakçı, Ş.; Ertaş, M.; Atalar, A. Ç.; Gümrü, S.; Karlı, N. (Frontiers in Neurology, 2024)
Migraine, a prevalent neurological disorder, affects approximately 14.1% of the global population and disproportionately impacts females. This debilitating condition significantly compromises quality of life, productivity, and incurs high healthcare costs, presenting a challenge not only to individuals but to societal structures as a whole. Despite advances in our understanding of migraine pathophysiology, treatment options remain limited, necessitating ongoing research into effective therapies. This review delves into the complexity of migraine management, examining the roles of genetic predisposition, environmental influences, personalized treatment approaches, comorbidities, efficacy and safety of existing acute and preventive treatments. It further explores the continuum between migraine and tension-type headaches and discusses the intricacies of treating various migraine subtypes, including those with and without aura. We emphasize the recent paradigm shift toward trigeminovascular activation and the release of vasoactive substances, such as calcitonin gene-related peptide (CGRP), which offer novel therapeutic targets. We assess groundbreaking clinical trials, pharmacokinetic and pharmacodynamic perspectives, safety, tolerability, and the real-world application of CGRP monoclonal antibodies and gepants. In the face of persisting treatment barriers such as misdiagnosis, medication overuse headaches, and limited access to specialist care, we discuss innovative CGRP-targeted strategies, the high cost and scarcity of long-term efficacy data, and suggest comprehensive solutions tailored to Turkiye and developing countries. The review offers strategic recommendations including the formulation of primary care guidelines, establishment of specialized outpatient clinics, updating physicians on novel treatments, enhancing global accessibility to advanced therapies, and fostering patient education. Emphasizing the importance of lifestyle modifications and holistic approaches, the review underscores the potential of mass media and patient groups in disseminating critical health information and shaping the future of migraine management.